Eyes on the Storm: How Climate Change Is Affecting Our Vision and What We Can Do About It: Doi: 10.36351/pjo.v40i3.1874 - Malik, Prof. Tayyaba Gul (Pakistan Journal of Ophthalmology, 2024)
Climate change refers to significant, long-term shifts in seasonal patterns and weather that occur over extended periods, even spanning millions of years.1Natural and human factors both significantly contribute to climate change. Natural factors include volcanic activity and ultraviolet radiation, while human factors encompass industrial and vehicular emissions, increasing solid waste generation, deforestation, unplanned urbanization, and population influx into large cities.